Effect of Ramadan environment on Fagerstrom Test For Nicotine Dependence (FTND) among smokers - Z., Nuraisyah Hani; Ismail, Suriani; Abd Manaf, Rosliza; A. F., Ahmad Farhan (Community Health Society Malaysia, 2016)
Background: Measurement of the nicotine dependence of the smokers can become valuable information in understanding the smoker’s level of addiction. One of the methods in measuring the nicotine dependence is by using the Fagerstrom Test for Nicotine Dependence (FTND). Understanding the accurate level of addiction level can help in the process of developing approach for smoking cessation. Approaches for smoking cessation intervention can be found during Ramadan where every Muslim is obligated to fast. Ramadan environment can provide a supportive environment for the smokers in smoking cessation. Materials and Methods: A total of 61 male smokers who currently smoke cigarette on daily basis were recruited. The study used the time-series experimental study design to evaluate the effect of Ramadan environment on FTND among a group of smokers who work at a local authority in Selangor. The data were collected three times which were one week before Ramadan, 21st of Ramadan and 21 days after Ramadan. The FTND questionnaire used in this study was already translated into Bahasa Malaysia and validated from previous study. Data analysis was conducted by using repeated measure One-way ANOVA and paired t-test. Result: The study showed a significant difference in the FTND score from before, during and after Ramadan (p = 0.003). From the post-hoc test, there is a significant decrease in the FTND score from before Ramadan to during Ramadan and also from before Ramadan to one month after Ramadan (p = 0.001, p = 0.002). Conclusion: The positive environment during Ramadan has helped to reduce the FTND score of the smokers. Health care professional should use this opportunity to help the smoker to quit smoking.